Chimerization at the AQP2–AQP3 locus is the genetic basis of melarsoprol–pentamidine cross-resistance in clinical Trypanosoma brucei gambiense isolates. Issue 2 (August 2015) - Graf, Fabrice E.; Baker, Nicola; Munday, Jane C.; de Koning, Harry P.; Horn, David; Mäser, Pascal
Highlights: Expression of AQP2 restores drug susceptibility in a resistant Trypanosoma brucei gambiense isolate. The AQP2/3 chimera from the resistant isolate does not complement AQP2 deletion. Hence AQP2/3 chimerization accompanied by loss of AQP2 is the cause of drug resistance. Graphical Abstract: Abstract: Aquaglyceroporin-2 is a known determinant of melarsoprol–pentamidine cross-resistance in Trypanosoma brucei brucei laboratory strains. Recently, chimerization at the AQP2–AQP3 tandem locus was described from melarsoprol–pentamidine cross-resistant Trypanosoma brucei gambiense isolates from sleeping sickness patients in the Democratic Republic of the Congo. Here, we demonstrate that reintroduction of wild-type AQP2 into one of these isolates fully restores drug susceptibility while expression of the chimeric AQP2/3 gene in aqp2–aqp3 null T.   b.   brucei does not. This proves that AQP2–AQP3 chimerization is the cause of melarsoprol–pentamidine cross-resistance in the T.   b.   gambiense isolates.